Biomaterials and tissue engineering in urology - Denstedt, John; Atala, Anthony 1958- (Woodhead Publishing in materials, 2009)
Patients with urological disorders should greatly benefit from the recent improvements to the biomaterials used in devices and the prospect of effective regenerative medicine. Biomaterials and tissue engineering in urology provides a comprehensive review of this important area.